DARI ANARKI KE HIRARKI: EKSPOSISI GAGASAN THOMAS HOBBES SEBAGAI RUJUKAN TEORI REALISME - Stenly Djatah (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2021)
In International Relation theory discourse, Classical Realism has some typical characteristics that differentiate it from other theories. The typical characteristics can be indicated by the ideas of Anarchy and Conflict. The two ideas in Classical Realism theory refers to Thomas Hobbes’ Political Philosophy on the State of Nature. Considering that the two ideas are only two of the entire ideas of Thomas Hobbes’ Political Philosophy, the State of Anarchy and Conflict in Classical Realism theory needs to be completed with other ideas. The writing has been made to show the function of ratio as a reason to seek peace in a hierarchical relation through Leviathan’s power. Therefore, it can be seen that Thomas Hobbes discusses not only about the state of anarchy but also the fact of hierarchical system urgency to avoid conflict.